2020
DOI: 10.9734/acri/2020/v20i530194
|View full text |Cite
|
Sign up to set email alerts
|

Practices of Nurses for the Care of Premature in Neonatal Intensive Care Unit: A Literature Review

Abstract: Objective: To analyze the nursing care provided to premature infants in the Neonatal Intensive Care Unit. Methods: Descriptive study with a qualitative approach, such as literature review. The selection of articles took place from August to October 2018. The searches resulted in the visualization of 75 articles. Of which only 12 articles met the established criteria and descriptors. Results: The main nursing care provided to premature infants in the NICU are: Observation of the premature infant, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…The current study results revealed that all the studied nurses selected head to toe assessment, basic & pediatric advanced cardiovascular life support, oxygen saturation measurement, high-risk and critical postoperative care as the most important critical care nursing skills at NICU & SPICU. This result was supported by Silva et al, (2020) who carried out a study entitled "Practices of Nurses for the Care of Premature in Neonatal Intensive Care Unit in Brazil" and mentioned that majority of the studied nurses selected head to toe assessment, basic& pediatric advanced cardiovascular life support, oxygen saturation measurement as the most important critical care nursing skills at NICU&SPICU. Also, this result was in agreement with Pour&Kaber, (2017) who studied "Learning and quality improvement : nursing in the pediatric intensive care unit in British Columbia" and mentioned that, the majority of the studied nurses selected trauma as most cases admitted to pediatric intensive and all of them selected head to toe assessment, basic & pediatric advanced cardiovascular life support, oxygen saturation measurement, tracheostomy care, high-risk and critical post-operative care a PICU.…”
Section: Figurementioning
confidence: 76%
“…The current study results revealed that all the studied nurses selected head to toe assessment, basic & pediatric advanced cardiovascular life support, oxygen saturation measurement, high-risk and critical postoperative care as the most important critical care nursing skills at NICU & SPICU. This result was supported by Silva et al, (2020) who carried out a study entitled "Practices of Nurses for the Care of Premature in Neonatal Intensive Care Unit in Brazil" and mentioned that majority of the studied nurses selected head to toe assessment, basic& pediatric advanced cardiovascular life support, oxygen saturation measurement as the most important critical care nursing skills at NICU&SPICU. Also, this result was in agreement with Pour&Kaber, (2017) who studied "Learning and quality improvement : nursing in the pediatric intensive care unit in British Columbia" and mentioned that, the majority of the studied nurses selected trauma as most cases admitted to pediatric intensive and all of them selected head to toe assessment, basic & pediatric advanced cardiovascular life support, oxygen saturation measurement, tracheostomy care, high-risk and critical post-operative care a PICU.…”
Section: Figurementioning
confidence: 76%